Seasonal variation of haemoglobin mass in internationally competitive female road cyclists - Garvican, L. A.; Martin, D. T.; McDonald, W.; Gore, C. J. (European Journal of Applied Physiology, 2010)
In order to quantify the seasonal variability of haemoglobin mass (Hbmass) in cyclists during a competitive season, and investigate whether variability is associated with changes in training load or performance, Hbmass was measured in 10 internationally competitive female road cyclists approximately once per month for 2-10 months via CO-rebreathing. Power meters were used to quantify daily load (Training Stress Scores) during training and racing, from which cumulative training load units for 7, 14, 28 and 42 day were calculated. Maximal mean power (MMP) for 1, 4, 10 and 25 min, performed during training or racing was used as a surrogate for performance. The relationship between changes in training load (Training) and changes in Hbmass, and between Hbmass and changes in MMP was established via regression analysis. Individual coefficients of variation (CV) in Hbmass ranged from 2.0 to 4.4%. The weighted mean CV in Hbmass was 3.3% (90% Confidence Limits: 2.9-3.8%) or 23 g over the average 6.6 ± 2.3 month monitoring period. The effect of Training on Hbmass was small for 7 and 14 day (r = 0.22 and 0.29), moderate for 42 day (r = 0.35) and large for 28 day (r = 0.56). The regression slope was greatest for 42 day, with a 10% change in training associated with a ~1% change in Hbmass. The relationship between Hbmass and MMP was ~0.5:1 for MMP1min,10min and 25min and ~1:1 for MMP4min, respectively. Hbmass varies by ~3% in female cyclists during a competitive season. Some of the variation may be related to oscillations in chronic training load.